Code Switching Linguistic Strategy in Agung Hapsah's YouTube Advertising Content - Situmorang, Ruben; Rosyidha, Alfin (Universitas Islam Negeri Palopo, 2025)
Digital marketing has been influenced by advances in information and technology. With this development, communication approaches are also evolving in digital media. Code switching is one of the linguistic phenomena that can be used as a communication strategy. Agung Hapsah is one of the YouTubers who uses Code Switch to advertise products expressively and interestingly. The purpose of this study is to identify and explore the types and functions of code switching applied and its linguistic functions in digital advertising. Engaging language can build brand image, increase sales and build rapport with audiences. This study uses a qualitative method to describe and identify the results of the analysis regarding the types and functions of code switching and its functions in digital advertising. The data source used is the transcription of 4 videos of Agung Hapsah, with an upload time of 2 years. The results of this study found 84 data of Agung Hapsah's speech that contain Code Switching with 79.76% type of intra sentential switching, 78.58% facility of Expression according to Marasigan (1983) and 80.95% solicitation or persuading as its linguistic function in digital advertising.